Pengaruh Kepedulian Remaja dalam Kegiatan Keagamaan dengan Pengamalan Keagamaannya, - Jimatul Arrobi; Hikmat Purnama; Eki Agustin; Muhamad Darusalam (CV. Syntax Corporation Indonesia, 2021)
Community religious activities are religious efforts or activities that include the process of developing diri, the soul and the ability of a person to produce moral andhigh-use output. The purpose of this study is to describe empirical facts about the concern of rw 01 purabaya village youth in participating in religious activities, their religious practice, andthe relationship of antaraboth variables. To measure the problem,his first variablesare participation, attention and contribution. While the second variable considers the indicators oftheir religious practice, namely the relationship with God, man and alam. Penelitian iniuses descriptive methods through observation, interview and questionnaire. While the data processing technique is carried out based on statistical analysis, namely correlation tests. From the results of data processing, rw 01 purabaya village has a high concern for religious activities in the community with a value of 4.1 and their religious practice which reaches a value of 4.0. Therefore, thereis asignificant relationship between rw 01 youth's concern for religious activities in the community and their religious practice. The relationship is intended with the value of the co-relation coefficientof0.73 which inthecategorywill have a high correlation becauseit is at intervals of 0.70 - 0.90. Meanwhile, the magnitude of the influence of adolescent concern for religious activities in the community to their religious practice by 31% and there are still 69% more influenced by other factors.